In Silico Docking Analysis of Selected Anti-Oxidant Compounds Against VEGF Protein - Joshi, Swati; Tufch, Neema; Rai, Nishant; Kumar, Navin (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*310.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929967);" role="presentation">Vascular <span dir="ltr" style="left: calc(var(--scale-factor)*110.66px); top: calc(var(--scale-factor)*310.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943934);" role="presentation">Endothelial Growth Factor <span dir="ltr" style="left: calc(var(--scale-factor)*222.77px); top: calc(var(--scale-factor)*310.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923941);" role="presentation">(VEGF) is a key regulator of vasculogenesis and angiogenesis. <span dir="ltr" style="left: calc(var(--scale-factor)*483.34px); top: calc(var(--scale-factor)*310.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953406);" role="presentation">Although, e<span dir="ltr" style="left: calc(var(--scale-factor)*76.46px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929274);" role="presentation">xpression of VEGF <span dir="ltr" style="left: calc(var(--scale-factor)*156.74px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922732);" role="presentation">is <span dir="ltr" style="left: calc(var(--scale-factor)*165.98px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.838296);" role="presentation">necessar<span dir="ltr" style="left: calc(var(--scale-factor)*199.97px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946164);" role="presentation">y for body functioning but <span dir="ltr" style="left: calc(var(--scale-factor)*308.11px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954);" role="presentation">its <span dir="ltr" style="left: calc(var(--scale-factor)*320.11px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895294);" role="presentation">overexpression <span dir="ltr" style="left: calc(var(--scale-factor)*383.23px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885739);" role="presentation">supports <span dir="ltr" style="left: calc(var(--scale-factor)*419.62px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873303);" role="presentation">oncogenesis. <span dir="ltr" style="left: calc(var(--scale-factor)*473.50px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911917);" role="presentation">Therefore, <span dir="ltr" style="left: calc(var(--scale-factor)*518.02px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.11022);" role="presentation">it <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94759);" role="presentation">has become a major target for <span dir="ltr" style="left: calc(var(--scale-factor)*202.13px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941816);" role="presentation">the development of <span dir="ltr" style="left: calc(var(--scale-factor)*285.89px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869085);" role="presentation">cancer <span dir="ltr" style="left: calc(var(--scale-factor)*316.03px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889004);" role="presentation">therapeutics<span dir="ltr" style="left: calc(var(--scale-factor)*364.27px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990621);" role="presentation">. Various anti-<span dir="ltr" style="left: calc(var(--scale-factor)*424.54px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944114);" role="presentation">VEGF compound<span dir="ltr" style="left: calc(var(--scale-factor)*496.78px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90709);" role="presentation">s have <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">been <span dir="ltr" style="left: calc(var(--scale-factor)*93.62px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939536);" role="presentation">explored for anti-<span dir="ltr" style="left: calc(var(--scale-factor)*164.18px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908317);" role="presentation">angiogenic properties and are presently under cl<span dir="ltr" style="left: calc(var(--scale-factor)*358.15px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961021);" role="presentation">inical trials. <span dir="ltr" style="left: calc(var(--scale-factor)*408.43px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902078);" role="presentation">The present study is focused <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*85.22px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.995438);" role="presentation">in si<span dir="ltr" style="left: calc(var(--scale-factor)*102.98px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1);" role="presentation">lico <span dir="ltr" style="left: calc(var(--scale-factor)*121.22px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939225);" role="presentation">analysis of various known antioxidants against VEGF-A, <span dir="ltr" style="left: calc(var(--scale-factor)*357.79px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908991);" role="presentation">using i<span dir="ltr" style="left: calc(var(--scale-factor)*385.51px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950194);" role="presentation">GEMDOCK software. Hesperidin <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885147);" role="presentation">has shown <span dir="ltr" style="left: calc(var(--scale-factor)*117.14px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960252);" role="presentation">minimum <span dir="ltr" style="left: calc(var(--scale-factor)*158.78px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927263);" role="presentation">binding energy -<span dir="ltr" style="left: calc(var(--scale-factor)*225.53px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936043);" role="presentation">121.04 kcal mol-1 <span dir="ltr" style="left: calc(var(--scale-factor)*299.23px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888085);" role="presentation">amongst <span dir="ltr" style="left: calc(var(--scale-factor)*336.07px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1);" role="presentation">all <span dir="ltr" style="left: calc(var(--scale-factor)*348.91px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917111);" role="presentation">antioxidants, <span dir="ltr" style="left: calc(var(--scale-factor)*403.15px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943529);" role="presentation">followed by quercetin (-<span dir="ltr" style="left: calc(var(--scale-factor)*500.98px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905709);" role="presentation">98.79 <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.991638);" role="presentation">kcal mol-1)<span dir="ltr" style="left: calc(var(--scale-factor)*117.02px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00409);" role="presentation">, gallic acid (-<span dir="ltr" style="left: calc(var(--scale-factor)*177.29px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977857);" role="presentation">77.49 kcal mol-1) <span dir="ltr" style="left: calc(var(--scale-factor)*253.01px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938054);" role="presentation">and ascorbic acid (-<span dir="ltr" style="left: calc(var(--scale-factor)*336.55px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977857);" role="presentation">68.42 kcal mol-1). <span dir="ltr" style="left: calc(var(--scale-factor)*414.82px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935076);" role="presentation">Hesperidin, a <span dir="ltr" style="left: calc(var(--scale-factor)*473.86px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943415);" role="presentation">known <span dir="ltr" style="left: calc(var(--scale-factor)*505.06px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934603);" role="presentation">anti- <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93553);" role="presentation">angiogenic compound, appeared <span dir="ltr" style="left: calc(var(--scale-factor)*213.65px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04428);" role="presentation">to be the <span dir="ltr" style="left: calc(var(--scale-factor)*259.85px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.854772);" role="presentation">best <span dir="ltr" style="left: calc(var(--scale-factor)*281.57px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988576);" role="presentation">inhibitor <span dir="ltr" style="left: calc(var(--scale-factor)*321.79px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04555);" role="presentation">of VEGF-A, <span dir="ltr" style="left: calc(var(--scale-factor)*380.35px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00576);" role="presentation">and may be <span dir="ltr" style="left: calc(var(--scale-factor)*438.46px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938592);" role="presentation">further <span dir="ltr" style="left: calc(var(--scale-factor)*471.22px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914151);" role="presentation">explored <span dir="ltr" style="left: calc(var(--scale-factor)*511.90px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*416.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907828);" role="presentation">development of anticancer drug.